The prehistory of Colorado and adjacent areas - Stone, Tammy, 1961- (University of Utah Press, 1999)
"The Prehistory of Colorado and Adjacent Areas is a short, accessible account of the state's human past. Based on the archaeological record, this book reconstructs past lifeways using current theory and explanations. Using a regional, rather than site-specific approach, it presents current explanations of what prehistoric Coloradans did at various points in time and why they changed."--Jacket